The Increasing Weight of Crohnʼs Disease Subjects in Clinical Trials: A Hypothesis-generatings Time-trend Analysis - Moran, Gordon W.; Dubeau, Marie-France; Kaplan, Gilaad G.; Panaccione, Remo; Ghosh, Subrata (Inflammatory bowel diseases, 2013)
The incidence of obesity is increasing worldwide. Recent evidence shows that the incidence of Crohn's disease (CD) is increasing as well. Adipocytes release a variety of proinflammatory cytokines and peptides. Visceral adiposity may play an important role in the initiation and perpetuation of inflammation in CD. We report on an analysis of body weight in CD clinical trials between 1991 and 2008. MEDLINE-based databases were searched for randomized controlled trials pertaining to CD. A time-trend analysis was carried out to investigate changes in weight and disease activity over time. Potential correlation between subject weight and clinical activity was studied. Forty randomized controlled trials involving a total of 10,282 patients with CD conducted between 1991 and 2008 were included. No significant change in gender distribution was noted throughout the follow-up. A significant increase in weight (r = 0.360; 95% confidence interval [CI]: 0.4556-0.8813) and body mass index (r = 0.1431; 95% CI: 0.02628-0.2272) was observed over the time period. Study subjects demonstrated a significant increase in clinical disease activity as measured by the Crohn's disease activity index (r = 0.1092; 95% CI: 2.101-9.087) and disease duration (r = 0.06340; 95% CI: 0.02421-0.2530) over the same time period. We demonstrate increasing body weight over time from 1991 to 2008 in CD as evidenced by baseline data from randomized clinical trials. Adiposity may play a potential role in initiating and perpetuating intestinal inflammation, a hypothesis that should be explored further.